Abrasion wear resistance of different artificial teeth opposed to metal and composite antagonists - Pâmela Carbone Mello; Abílio Ricciardi Coppedê; Ana Paula Macedo; Maria da Gloria Chiarello de Mattos; Renata Cristina Silveira Rodrigues; Ricardo Faria Ribeiro (University of São Paulo, 2009)
One of the most important properties of artificial teeth is the abrasion wear resistance, which is determinant in the maintenance of the rehabilitation's occlusal pattern. OBJECTIVES: This in vitro study aims to evaluate the abrasion wear resistance of 7 brands of artificial teeth opposed to two types of antagonists. MATERIAL AND METHODS: Seven groups were prepared with 12 specimens each (BIOLUX & BL, TRILUX & TR, BLUE DENT & BD, BIOCLER & BC, POSTARIS & PO, ORTHOSIT & OR, GNATHOSTAR & GN), opposed to metallic (M & nickel-chromium alloy), and to composite antagonists (C & Solidex indirect composite). A mechanical loading device was used (240 cycles/min, 4 Hz speed, 10 mm antagonist course). Initial and final contours of each specimen were registered with aid of a profile projector (20x magnification). The linear difference between the two profiles was measured and the registered values were subjected to ANOVA and Tukey's test. RESULTS: Regarding the antagonists, only OR (M = 10.45 ± 1.42 µm and C = 2.77 ± 0.69 µm) and BC (M = 6.70 ± 1.37 µm and C = 4.48 ± 0.80 µm) presented statistically significant differences (p < 0.05). Best results were obtained with PO (C = 2.33 ± 0.91 µm and M = 1.78 ± 0.42 µm), followed by BL (C = 3.70 ± 1.32 µm and M = 3.70 ± 0.61 µm), statistically similar for both antagonists (p>0.05). Greater result variance was obtained with OR, which presented the worse results opposed to Ni-Cr (10.45 ± 1.42 µm), and results similar to the best ones against composite (2.77 ± 0.69 µm). CONCLUSIONS: Within the limitations of this study, it may be concluded that the antagonist material is a factor of major importance to be considered in the choice of the artificial teeth to be used in the prosthesis.